(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study examines to test asymmetry of income and wealth inequality on GDP growth rate in India during 1995-2023 through NARDL model. Methods: The paper applied Shin et al. (2014) model to estimate asymmetry in NARDL model, applied Dicky and Fuller (1979) model for unit root test, applied Breusch-Pagan model (1979) to test the serial correlation and heteroscedasticity tests. Stability test was done by following Page (1954). Symmetry test was applied by using Wald test (1943). The data on income inequality and wealth inequality were collected from the World Inequality Data Lab and data on GDP growth rate were collected from the World Bank. Results: The paper finds that positive and negative changes of cumulative dynamic multipliers of both income and wealth inequality impact on GDP growth favourably and adversely. Positive and negative responses diverge away from positive and negative long run limits and asymmetry lines of wealth and income inequality have no convergence. Cointegration of wealth and income inequality have negative impacts on GDP growth rate. Conclusion: NARDL model can help policy makers to conduct fiscal and monetary policy and other welfare measures in both short run and long run to ameliorate inequalities towards sustainable GDP growth rate. The model can justify how positive and negative responses of asymmetries in short and long run affect GDP growth.